2007
DOI: 10.1152/japplphysiol.00616.2006
|View full text |Cite
|
Sign up to set email alerts
|

Microinjection of DLH into the region of the caudal ventral respiratory column in the cat: evidence for an endogenous cough-suppressant mechanism

Abstract: Poliacek I, Wen-Chi Corrie L, Wang C, Rose MJ, Bolser DC. Microinjection of DLH into the region of the caudal ventral respiratory column in the cat: evidence for an endogenous cough-suppressant mechanism. J Appl Physiol 102: 1014 -1021, 2007. First published November 30, 2006; doi:10.1152/japplphysiol.00616.2006.-The caudal ventral respiratory column (cVRC) contains premotor expiratory neurons that play an important role in cough-related expiratory activity of chest wall and abdominal muscles. Microinjection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 44 publications
12
35
0
Order By: Relevance
“…9,10,27,43,45,47,53,54). As already mentioned, these responsive structures may comprise, in particular, the caudal ventral respiratory group, in agreement with our previous suggestions (11,43) and those by Bolser and colleagues (9,48). Present results do not allow us to support or to refute the notion of the existence of a coughgating mechanism or any particular pool of neurons specifically relevant to this function.…”
Section: Perspectives and Significancesupporting
confidence: 89%
“…9,10,27,43,45,47,53,54). As already mentioned, these responsive structures may comprise, in particular, the caudal ventral respiratory group, in agreement with our previous suggestions (11,43) and those by Bolser and colleagues (9,48). Present results do not allow us to support or to refute the notion of the existence of a coughgating mechanism or any particular pool of neurons specifically relevant to this function.…”
Section: Perspectives and Significancesupporting
confidence: 89%
“…We also proposed (42) that several neural substrates involved in the regulation of cough (12,16,17,31,44,46,48,56,57) may be sites of action of antitussive drugs. In agreement with our previous suggestion and preliminary results (17,42,44) as well as the proposal by Bolser and colleagues (12,49), the responsive sites may comprise, in particular, the caudal part of the ventral respiratory column (2), i.e., the so-called caudal ventral respiratory group (cVRG), where bulbospinal expiratory neurons are concentrated (6,30,63).…”
supporting
confidence: 92%
“…Interestingly, Poliacek et al (49) showed that unilateral microinjections of DLH into the cVRG of anesthetized cats reduced cough number and associated abdominal thrusts, thus revealing the presence of a cough-suppressant neuronal network within this region. Furthermore, in agreement with previous suggestions (12,17,42,44,49), codeine within the cVRG region proved to have an antitussive effect without a direct action on bulbospinal expiratory neurons (51).The present research was undertaken on pentobarbital-anesthetized, spontaneously breathing rabbits with the main purpose of ascertaining whether the cVRG could be a site of action of different centrally acting antitussive agents and a component of the neural system involved in cough regulation. We used the same antitussive agents already tested within the cNTS (42).…”
supporting
confidence: 79%
“…In all instances, no appreciable changes in the pattern of breathing and cough responses were observed. In particular, it is worth noting that galanin and galnon did not cause any significant effect on the cough reflex when microinjected into the caudal ventral respiratory group, a widely recognized site of action of centrally acting antitussive drugs and a neural structure with a prominent role in the regulation of the cough reflex (see e.g., 9,13,14,41,42,48,50).…”
Section: Galnon-induced Effects On Device-induced Cough Responsesmentioning
confidence: 99%
“…Studies undertaken to provide insights into the neural mechanisms subserving the cough reflex may also provide useful suggestions for novel antitussive therapeutic strategies. The cough reflex involves several brain stem structures that also underlie respiratory rhythm generation (e.g., 7,9,10,19,24,27,[47][48][49]55). …”
mentioning
confidence: 99%